Differences in the Supply Chain Financial Performance of BUMDes Indonesia and Desa Lestari Malaysia - Kusmantini, Titik; Robani, Anida; Sutiono, Heru Tri; ., Zuhrotun; Viyani, Ari Okta; Rahmatullah, Arwin Yafi (Journal of Ecohumanism, 2025)
Assessing differences in supply chain financial performance between BUMDes in Indonesia and Desa Lestari in Malaysia is also critical to understanding the effectiveness of local economic initiatives. This comparison can reveal insights into operational efficiency, resource management, and overall financial health, which are critical for sustainable development. This study will compare the supply chain financial performance of BUMDes in Indonesia with that of Desa Lestari Malaysia. Data were collected using survey techniques and analyzed using SPSS and the t-test. The results show significant differences between BUMDes in Indonesia and Desa Lestari in Malaysia regarding financing interest and financing volume. However, both systems show similarities in financing availability and period, indicating similar efforts to support the village economy. These findings provide important insights for developing village financial management policies and strategies in both countries. Assessing differences in supply chain financial performance between BUMDes in Indonesia and Desa Lestari in Malaysia is also critical to understanding the effectiveness of local economic initiatives. This comparison can reveal insights into operational efficiency, resource management, and overall financial health, which are critical for sustainable development. This study will compare the supply chain financial performance of BUMDes in Indonesia with that of Desa Lestari Malaysia. Data were collected using survey techniques and analyzed using SPSS and the t-test. The results show significant differences between BUMDes in Indonesia and Desa Lestari in Malaysia regarding financing interest and financing volume. However, both systems show similarities in financing availability and period, indicating similar efforts to support the village economy. These findings provide important insights for developing village financial management policies and strategies in both countries.